2019
DOI: 10.3390/catal9010052
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Synthesis and Characterization of Metal Organic Frameworks for Photocatalytic Water Purification

Abstract: This review analyzes the preparation and characterization of metal organic frameworks (MOFs) and their application as photocatalysts for water purification. The study begins by highlighting the problem of water scarcity and the different solutions for purification, including photocatalysis with semiconductors, such as MOFs. It also describes the different methodologies that can be used for the synthesis of MOFs, paying attention to the purification and activation steps. The characterization of MOFs and the dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
179
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(182 citation statements)
references
References 232 publications
0
179
0
3
Order By: Relevance
“…The high concentration of organic dyes in wastewater has been a problem; synthetic dyes are recalcitrant compounds and are not completely degraded by conventional water treatments [1,2]. Currently, the search for efficient, cheap, and green treatment processes for wastewater is a challenge around the world.…”
Section: Introductionmentioning
confidence: 99%
“…The high concentration of organic dyes in wastewater has been a problem; synthetic dyes are recalcitrant compounds and are not completely degraded by conventional water treatments [1,2]. Currently, the search for efficient, cheap, and green treatment processes for wastewater is a challenge around the world.…”
Section: Introductionmentioning
confidence: 99%
“…In this field, technologies like ultraor nanofiltration are able to remove macromolecules and biological matter, while inorganic ions can be separated by reverse osmosis. However, those processes are characterized by high power consumption, increasing operational costs [13]. The biological treatment of wastewater mainly includes the use of biological activated sludge for promoting the biochemical degradation routes of the different pollutants.…”
Section: Water Purification By Photocatalysismentioning
confidence: 99%
“…This is not the case for titanium dioxide (TiO2), the most used and researched photocatalyst. TiO2 has been utilized for both air and water purification [31,32]. This semiconductor is characterized by high activity in photocatalysis, besides high chemical stability and low biological toxicity [33,34].…”
Section: Water Purification By Photocatalysismentioning
confidence: 99%
“…In addition, Salama et al, reported an SO2 gas sensor while using an MOF [12]. Metal-organic frameworks (MOFs) have a wide range of interesting properties such as high specific surface area and facile modification [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. MOFs are microporous materials that form three-dimensional (3D) crystalline networks, which are prepared by combining various metal ions with organic linkers in an appropriate solvent [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%